2014
DOI: 10.1108/jmlc-11-2013-0045
|View full text |Cite
|
Sign up to set email alerts
|

To be corrupt or not to be corrupt

Abstract: If you would like to write for this, or any other Emerald publication, then please use our Emerald for Authors service information about how to choose which publication to write for and submission guidelines are available for all. Please visit www.emeraldinsight.com/authors for more information. About Emerald www.emeraldinsight.comEmerald is a global publisher linking research and practice to the benefit of society. The company manages a portfolio of more than 290 journals and over 2,350 books and book series … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
42
0
4

Year Published

2016
2016
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 45 publications
(46 citation statements)
references
References 30 publications
0
42
0
4
Order By: Relevance
“…It suggests a considerable shift in thinking about the causes of corruption and corruption-control initiatives is needed. In their review on corruption research, Andvig et al (2001, p. 39) concluded that "in recent years, economic explanations of corruption have been the most cited and probably also the most influential for policy formulations" (see also (Prabowo 2014;Shover and Bryant 1993;Dimant 2013;Svensson 2005)). Present organizational anti-corruption approaches appear to rest heavily on deterrence-detecting and punishing transgressions-and on diminishing opportunities for engaging in corruption-e.g., the 'four-eyes-policy'.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…It suggests a considerable shift in thinking about the causes of corruption and corruption-control initiatives is needed. In their review on corruption research, Andvig et al (2001, p. 39) concluded that "in recent years, economic explanations of corruption have been the most cited and probably also the most influential for policy formulations" (see also (Prabowo 2014;Shover and Bryant 1993;Dimant 2013;Svensson 2005)). Present organizational anti-corruption approaches appear to rest heavily on deterrence-detecting and punishing transgressions-and on diminishing opportunities for engaging in corruption-e.g., the 'four-eyes-policy'.…”
Section: Discussionmentioning
confidence: 99%
“…Various disciplines have postulated explanations for why some individuals are more prone to corruption than others, specifically economics, criminology, and social psychology (Gorsira et al 2016). The most prominently explanations include incentives (Dong et al 2012;Prabowo 2014;Shover and Bryant 1993;Andvig et al 2001;Dimant 2013), opportunities (see, for instance, Aguilera and Vadera 2008;Pinto et al 2008;Graycar and Sidebottom 2012), and norms (see, for instance, Powpaka 2002; Köbis et al 2015;Rabl and Kühlmann 2008;Tavits 2010). A recent study demonstrated that all of these factors were, indeed, related to proneness to corruption (Gorsira et al 2016).…”
Section: Individual Factors Explaining Corruptionmentioning
confidence: 99%
“…So that families, communities and law enforcers work together to build a nation and state without corruption. Yogi Prabowo (2014), states that The Corruption Eradication Commission (KPK) formulated its corruption eradication strategy which covers four main areas, namely: 1) The field of institutional development; 2) Prevention field; 3) Actions; 4) The field of community participation.…”
Section: Justicementioning
confidence: 99%
“…This creates a strong motivation to defraud. After having the motivation and availability of opportunity, fraud can be used as a solution to the problems (Prabowo, 2014). The emerging opportunities are linked to the weakness of the organization's control system with a low probability of knowing.…”
Section: Fraudmentioning
confidence: 99%
“…Rationalization is needed so that the perpetrator can accept the unlawful behavior to keep the identity as a trusted person. Opinion of rationalization has various types such as "I deserve it", "management does not care about me", "no one is hurt", "this is to help the company" (Prabowo, 2014).…”
Section: Fraudmentioning
confidence: 99%